E-cigarettes use in the United States: reasons for use, perceptions, and effects on health - Sakshi Sapru; Mridula Vardhan; Qianhao Li; Yuqi Guo; Xin Li; Deepak Saxena (BMC, 2020)
Abstract Background Many researchers claim electronic cigarettes (e-cigarettes) to be a breakthrough invention for tobacco users that aspires to curb their addiction to conventional cigarettes. Claimed to be safer by their promoters, these smokeless devices have become increasingly popular since their arrival on the market among users of all ages, especially adolescents. This paper investigated the trends in e-cigarette usage since the time it arrived in the United States, highlighting the highest surge that has occurred in adolescent e-cigarette use. It also aimed to understand the reasons and perceptions behind the ever-increasing use of e-cigarettes by adolescents. Main body With the advent of e-cigarettes and common positive perceptions regarding their use, we are at risk of reversing the years of efforts regarding tobacco control and instead advance towards a new addiction with currently unknown long-term health hazards. There is substantial data showing a significant increase of e-cigarette users in the United States, especially among adolescents. The aim of this review was to explore the reasons behind this widespread increase in the use of e-cigarettes among the teenage population in the US and also to uncover the common perceptions about these new electronic delivery systems. In addition, this review attempted to summarize health benefits and hazards associated with e-cigarette use as it crucial to have the right information among its users regarding the health effects of e-cigarette use. Conclusion E-cigarettes are more appealing than c-cigarettes for a variety of reasons, including cost, choice of different flavors, ease of accessibility, and use and impact of social media. There are also different perceptions among e-cigarette users, including both adolescents and adults. The former group may use them because of the sense of fashion associated with this novel device, and the latter might intend to quit conventional/combustible cigarettes (c-cigarettes) by switching to e-cigarettes. However, it is important to note that e-cigarettes are a recent phenomenon; therefore, there is a lack of many long-term studies that can identify future health risks associated with e-cigarette use. We need more detailed studies that focus on the long-term health effects of e-cigarette use. Moreover, with the ever-increasing usage of e-cigarettes by adolescents (10 and 19 years), it is very important that e-cigarettes be incorporated into the current tobacco-free laws and ordinances. We conclude by stating that e-cigarettes need stronger regulations to prevent youth access and use.